Kesulitan Belajar Bahasa Arab Bagi Lulusan Sekolah Umum pada Prodi Pendidikan Bahasa Arab UINSI Samarinda - Lutfi Rosida Ramadanti; Khairy Abusyairy; Syarifaturrahmatullah Syarifaturrahmatullah (Borneo Journal of Primary Education, 2021)
Many public school alumni students still have not mastered basic Arabic lessons such as difficulties in listening, speaking, reading and writing Arabic and they also have difficulty memorizing vocabulary. So the researcher wants to know more about the problems of learning Arabic for public school alumni in the Arabic Language Education Study Program. The objectives of this study are: 1) To find out what problems or obstacles students face. 2) To find out the supporting factors and inhibiting factors of students. 3) To find out how to overcome the problems faced by students. Researchers used a qualitative approach in this study with a descriptive method. And the data collection instruments in this study are: Interviews and Documentation. The results of the research on the problems of learning Arabic for public school alumni students are that students do not have a basic Arabic language, students are not familiar with Arabic, and students lack self-confidence. Supporting factors in student learning: 1) Lecturers who are experts in their fields and always motivate students. 2) Lecturers not only provide material in class but also distribute material for study at home. Inhibiting factors in student learning: 1) Student study hours are not enough just in class. 2) Lack of self-awareness of students to continue learning Arabic. Efforts to overcome the problems of learning Arabic for public school alumni: 1) Adding study hours outside the classroom either self-taught, studying with friends, or taking courses. 2) Motivate yourself to continue learning Arabic